Essential Self-Breast Examination for Both Men and Women - Sujata Japannavar; Sujatha V (International Journal of Midwifery Nursing And Practices, 2023)
Breast self-examination stands as a crucial and foundational technique for the early detection of irregularities within the breast tissue, including both the breast itself and the nipple. This method is accessible and relevant to individuals of all genders, involving fundamental principles of observation and palpation. Those well-versed in breast self-examination possess the knowledge to guide others in this practice, which can lead to early intervention and, ultimately, the prevention of issues and complications related to the mammary gland. In many developing nations, the principles of breast self-examination offer an excellent approach for individuals to proactively monitor their breast health. This review article aims to provide a concise yet comprehensive guide for both men and women, empowering them with the necessary knowledge and skills to perform effective breast self-examinations. By doing so, individuals can take proactive steps in safeguarding their breast health, emphasizing the significance of early detection and intervention in the prevention of breast-related concerns and complications.
Keywords: Breast self-examination; breast tissue; concerns and complications; detection and intervention; mammary gland